Analyzing Land Use and Land Cover Changes and its Dynamics in Mokokchung District, Nagaland. - Latonglila Pongen,; Sentiakum Jamir,; M.S Rawat,; Sangyu Yaden, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Land use and land cover are crucial factors in comprehending the interactions of human activities with the environment, and thereby, it is essential to be able to simulate changes.GIS and remote sensing developments have made it possible to map and identify changes in land cover and use. This study aims to assess the changes in the land cover and land use in the Mokokchung District of Nagaland, northeastern India, during a thirty-year period. The analysis shows significant changes in land cover and use. The study used LANDSAT Imageries of 2003 and 2023 obtained from USGS Earth Explorer. Five LULC Classes- Forest, Agriculture, Settlement, Water Bodies, and Barren Land were identified and used to map the entire study area. Forest area cover the maximum total geographical area with 89% followed by built up and agricultural area each covering 5% and 3% of the total geographical area respectively. Over the years forest area has decline significantly whereas built up area has seen a major surge in its area.
Keywords: Land Cover; Land Use; Change Analysis; satellite image